Cost-effectiveness of universal repeat human immunodeficiency virus screening in pregnancy: A cross-sectional study from Western India - U C Samudyatha; J K Kosambiya; Harshad M Patel (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of the study was to evaluate the cost-effectiveness of universal repeat human immunodeficiency virus (HIV) screening late in pregnancy as opposed to the existing system of single HIV test early in pregnancy. Background: Strategy of universal repeat HIV screening in pregnancy to achieve Elimination of mother to child transmission in a low prevalence setting such as India should be examined from the cost-effectiveness point of view. Methodology: In a cross-sectional study, 2500 pregnant women with 32 weeks gestation or more and screened HIV nonreactive at least 3 months before the study were offered repeat HIV screening. A decision analysis model was used to determine cost-effectiveness of a repeat HIV screening late in pregnancy in both government (societal) and healthcare payer perspectives, followed by one-way sensitivity analysis at different rates of incident HIV in pregnancy. Results: The incidence of HIV infection during pregnancy was 1.18/1000 women years (95% confidence interval: 0.29-4.7). The existing system of single HIV test is 1.9 times costlier per quality adjusted life years gained than the proposed system of repeat HIV screening. Conclusion: When the incidence of HIV in pregnancy is 1.18/1000 woman-years, even in settings with antenatal HIV positivity rates as low as 0.01%, repeat HIV screening in pregnancy is cost effective.